Practical chemistry: a course for 'o' level volume 1 (revised) - Rasanayagam, L. J. (Federal Publications Singapore, 2004)
"Practical Chemistry: A Course for 'O' Level" is a comprehensive guide designed to help students master the practical aspects of chemistry, offering clear instructions, safety guidelines, and experimental techniques to prepare for the O-Level Chemistry exam.